Pre-straining effect on yielding behaviour of low-carbon steels - Zulkifli, Ahmad Shukron (2009)
Roll forming is yet used widely in the industry yet known to the world. It has complexity to design the product but it can be study and determined by evaluating and studying the mechanical properties on the stress-strain curve of the material. The study show how on the specimen that is setting up for a variable different pre- staining stages indicates that stress-strain curve help the designer to identify the yielding region effect on the bending deformation of the product while some defects such as springback will occur. The findings of this method can be relates to roll forming process in terms of stages and bending phenomenon that are something that is occur when doing roll forming process could lower the percent of defect for the products made by roll forming machine.